A Study on Cognitive Affordance Analysis and BX Design of Flight Reservation Application UI - et.al, Joon-woo Park (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study checked whether the application of the affordance design, which may improve the usability of the flight reservation application user, affects the brand's value, reliability, and loyalty, and sought an effective UI design plan of the flight reservation application. Researchers also checked the trend of changes in the flight reservation environment through theoretical study, and derived factors to analyze the impact of affordance design on user experience and brand experience. As for main analysis, the effect of the affordance design factor on the user experience and the effect of the usability factor on the brand experience has been checked using statistical analysis, and the effect priority of the affordance design factor by usability factor and the effect priority of the usability factor by brand experience factor have been derived. In the flight reservation application design, the application of the affordance design was identified to have a positive effect on the user experience. In terms of ease of learning, efficiency and memorization, the learning form and the use of metaphor were ranked high, and in the case of error prevention, contextual continuity and use correlation were analyzed as important factors. In satisfaction, all affordance factors were analyzed to form a relatively high satisfaction. The usability factors of the affordance design showed a high degree of effect on the brand's value, reliability and loyalty, and in particular, satisfaction and error prevention were identified as the most direct factor influencing the brand experience